Image of Navai and Artistic Interpretation in the Drama "Navai and Baykara" - Gulbahor Ashurova (International Journal on Integrated Education, 2022)
This article is devoted to the issue of creating historical dramas in Uzbek literature, the assessment given by him, the features of the representation of the image of Navai in Uzbek dramas of the period of independence. In particular, the issue of artistic interpretation of the image of Navai in the drama of Muhammad Ali "Navai and Baikara" is covered in detail.